E. Bláhová, Nejstarší staroslovenské homilie (Syntax a lexikon) - Stefanović, Dimitrije E. (Balcanica - Annual of the Institute for Balkan Studies, 2023)
Emilie Bláhová, Nejstarší staroslovenské homilie (Syntax a lexikon) [The Oldest Old Slavonic Homilies (Syntax and Lexicon)], Czechoslovak Academy of Sciences, Praha, 1973, pp. 93.